(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Information Literacy (IL) skills, defined as a set of skills to recognise at the point when data is required and can find, assess, and utilize the data required successfully. The study participants were diploma-level engineering students who had spent at least three semesters at Chamarajanagar District Government College. Information was gathered utilizing a Mittermeyer-adjusted study instrument and located utilizing a reference examination of understudy book indices in a paper task. The findings of this study show that respondents seriously lacked the knowledge and skills needed to evaluate internet data, identify the most effective search strategy, use academic resources, and ethically use information. It is proposed to use a larger sample of students to be more representative of the population of engineering students.